PENGUKURAN MUTU LAYANAN TERHADAP KEPUASAN KONSUMEN TOKO RITEL INDOMARET X KOTA SURAKARTA - Suhendro, Suhendro; Setyawanti, Dandang; Jati, Agung Nugroho; Tasari, Tasari (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2022)
This research study aimed at revealing perception on public’s satisfaction index to the service quality of Indomaret Retail X Surakarta from the dimension of tangibles, reliabilities, responsiveness, assurance and empathy. The population is all community members living in the Surakarta areas who have reported the research samples are 95 respondents that have been established using Cronin and Taylor’s Weighted Servqual formulation. The sampling applies the purposive sampling. The data are collected by means of quetionnaire with 6-scale of confirmation index to obtain the data of customers satisfaction index-tangibles, reliabilities, responsiveness , assurance and empathy each instrument has been examined and has fulfilled the validity and reliability standard through the Hoyt program, SPSS of 21. Servqual has started with the concept of services quality and has demonstrated the model of services quality gaps. This research tries to identify the most important dimension and perception of external customers towards the Indomaret Retail X Surakarta. The result shows that most servqual model factor, reliabilities are less satisfied than it should be